2003
DOI: 10.1074/jbc.m212321200
|View full text |Cite
|
Sign up to set email alerts
|

JAK2/STAT3, Not ERK1/2, Mediates Interleukin-6-induced Activation of Inducible Nitric-oxide Synthase and Decrease in Contractility of Adult Ventricular Myocytes

Abstract: Interleukin (IL)-6 decreases cardiac contractility via a nitric oxide (NO)-dependent pathway. However, mechanisms underlying IL-6-induced NO production remain unclear. JAK2/STAT3 and ERK1/2 are two well known signaling pathways activated by IL-6 in non-cardiac cells. However, these IL-6-activated pathways have not been identified in adult cardiac myocytes. In this study, we identified activation of these two pathways during IL-6 stimulation and examined their roles in IL-6-induced NO production and decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
119
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(124 citation statements)
references
References 44 publications
4
119
0
1
Order By: Relevance
“…38 Similar to the mechanisms of the inflammatory response in cardiac muscle, we found that sepsis significantly increased Stat3 phosphorylation in diaphragm, and importantly, that this increase was attenuated with nanoparticle treatment ( Figure 4A). Likewise, increases in NO have been shown to directly impair contractile function in a number of different skeletal muscles including the diaphragm.…”
Section: Discussionmentioning
confidence: 49%
“…38 Similar to the mechanisms of the inflammatory response in cardiac muscle, we found that sepsis significantly increased Stat3 phosphorylation in diaphragm, and importantly, that this increase was attenuated with nanoparticle treatment ( Figure 4A). Likewise, increases in NO have been shown to directly impair contractile function in a number of different skeletal muscles including the diaphragm.…”
Section: Discussionmentioning
confidence: 49%
“…Neutralization of CNS IL-6 attenuates traumatic spinal cord injury in rats and is associated with reduced iNOS activity (9). As has been seen in other tissues (10), IL-6 within the CNS may stimulate iNOS expression, resulting in the production of NO and leading to free radical-induced tissue injury (10).…”
Section: Introductionmentioning
confidence: 99%
“…Once formed, the IL-6/IL-6R/ gp130 complex stimulates the following 2 main signal transduction cascades that lead to activation of a number of transcription factors responsible for IL-6-mediated effects: JAK/STAT and Ras/MEK/ MAPK (11). IL-6-induced activation of the JAK2/STAT3 signaling pathway in cardiac myocytes results in activation of iNOS with subsequent NO production and decreased cardiac contractility (10).…”
Section: Introductionmentioning
confidence: 99%
“…The serine protease, elastase, is a major contributor to neutrophil-mediated damage, and hydrolyzes the extracellular matrix components elastin, fibronectin and collagen types III and IV [23]. Neutrophil elastase induces production of cytokines which decreases cardiac contractility via a nitric oxide-dependent pathway [1], and produces toxic mediators such as reactive oxygen species (ROS) [24]. ROS is strongly implicated in the pathogenesis of myocardial stunning, necrosis, apoptosis and vascular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil elastase is also known to induce production of cytokines, such as interleukin (IL)-6, which decreases cardiac contractility via a nitric oxide-dependent pathway [1]. Neutrophil elastase has been shown to be released in early stages of postischemic myocardial reperfusion in animal models [2], as well as during unstable angina attacks after myocardial infarction or cardiopulmonary bypass surgery in humans [3].…”
Section: Introductionmentioning
confidence: 99%